Robust design of breast scintigraphy collimator using Monte Carlo Simulations and response surface methodology - Balta, Sinem. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2007., 2007)
Breast Scintigraphy, a nuclear medicine breast imaging technique, is a supplemental breast exam that is used in patients to investigate a breast abnormality. It is not a primary investigative tool for breast cancer but it is used as a complementary technique in cases where conventional x-ray mammography has some limitations in breast cancer diagnosis. However, studies show that breast scintigraphy does not give successful results when breast abnormality is less than 1cm. The collimator plays an important role in image construction. This study aims to make a robust design of the breast scintigraphy system collimator to obtain a better image quality in small breast lesions (<1cm) by the optimization of the collimator parameters such as hole length (collimator length), hole size and septal thickness while keeping the lesion detectability less susceptible to patient variations such as breast and lesion dimensions. The breast and the lesion were modeled as a cylinder and a sphere, respectively. Monte Carlo Simulation is utilized for simulating the imaging system and Response Surface Methodology is applied for robust optimization. The first part of the study deals with a typical case of breast and lesion dimensions whereas the second part inserts variance to the parameters. Our results show that a hole length of 1.74cm, a hole size of 0.14cm and a septal thickness of 0.02cm are the dimensions of a robust collimator.|Keywords: Breast Scintigraphy, collimator, Monte Carlo Simulation, Response Surface Method, robust design
Keywords: Breast -- Radioisotope scanning.; Monte Carlo method.; Response surfaces (Statistics); Nuclear medicine.